Rancang Bangun Alat Buka Tutup Gorden 3 Model Menggunakan Mikrokontroler Berbasis Android - Syarifuddin Baco; Nur Alamsyah; Sukirman, Sukirman; Ahmad Martani; Indi Irwan Achmad; Muh. Taufiq Kurahman (Ikatan Ahli Informatika Indonesia, 2023)
Sunlight to change clean air is really needed in the morning and at night when you need to rest at home. Curtains, often referred to as blinds, are an important part of the home as an interior in offices, hotels, hospitals and high-rise buildings as protection from direct sunlight. Curtains are an element of the home, the office is always opened and closed, requiring energy and time to arrange them neatly. This work requires a technological innovation that helps make the work easier. The aim of the research is to speed up the work process in households or employees, office employees because in the morning after the sun shines and the sensor is exposed to light, the curtains open automatically. In the afternoon the sensor is not exposed to light, then the curtains automatically close without having to come and do it with human hands. The method used in this research is (Research & Development, R&D) with an assessment of development, namely opening curtains with three models, namely open front curtains with 2 models, namely separate right and left sides. Meanwhile, the back curtain (second layer) was controlled via Android with the Blynk application with several experimental tests carried out. The front curtains can be controlled via Android with 2 models that can be opened completely or little by little to the right or left. The research results show that the curtains can be opened and closed with control via the Android application and automatically using the LDR (Light Dependent Resistor) sensor and controlled via Android, thus providing clear information when the curtains are actually opened or closed.